1970
DOI: 10.1002/pol.1970.150080203
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of cerium (IV) oxidation of glucose and cellulose

Abstract: Cerium (IV) oxidations of model compounds for the hydroxylic functional groups of cellulose were conducted in 1.0M perchloric acid. Glucose, the model selected for the reducing end group, was oxidized 360 times faster than Schardinger β‐dextrin, the model for anhydro‐D‐glucose repeating units. In the presence of a fourfold excess of glucose, stoichiometry indicated specific conversion to arabinose; the competitive oxidation of arabinose produced is insignificant. Specific C1–C2 bond cleavage was also indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(42 citation statements)
references
References 37 publications
1
41
0
Order By: Relevance
“…The lower activation energy for the cerium-treated towels compared to the untreated towels in nitrogen appears to indicate that the cerium(IV) is functioning as an oxidant in the absence of oxygen, and the treated towels are undergoing oxidation reactions in addition to pyrolytic reactions. Cerium(IV) nitrate is known to oxidize cellulose model compounds in acidic solution [8]. This hypothesis is further supported by the observation that the cerium-containing ashes glow brightly after the experiment when they are exposed to air.…”
Section: Discussion Of Kinetic Parametersmentioning
confidence: 78%
See 1 more Smart Citation
“…The lower activation energy for the cerium-treated towels compared to the untreated towels in nitrogen appears to indicate that the cerium(IV) is functioning as an oxidant in the absence of oxygen, and the treated towels are undergoing oxidation reactions in addition to pyrolytic reactions. Cerium(IV) nitrate is known to oxidize cellulose model compounds in acidic solution [8]. This hypothesis is further supported by the observation that the cerium-containing ashes glow brightly after the experiment when they are exposed to air.…”
Section: Discussion Of Kinetic Parametersmentioning
confidence: 78%
“…For example, Hanna et al [11] have studied the thermal properties of cellulose triacetate with Ni(II), Cu(II), Co(II), and Cr(III), all poor oxidants, and found that they formed complexes that were thermally more stable than SELF-HEATING HAZARDS OF CERIUM(IV) NITRATED TREATED TOWELS 367 non-complexed cellulose triacetate. In addition, Pottenger and Johnson [8] studied the mechanism of cerium(IV) oxidation of glucose and cellulose. They determined that in solution, the cellulose model compounds were oxidized by formation of a cerium(IV) chelate, disproportionation to form a free radical, and then further oxidation by another cerium(IV) ion.…”
Section: Discussion Of Kinetic Parametersmentioning
confidence: 99%
“…It is an established fact that the redox-initiated process of graft copolymerization onto the polysaccharide backbone generates free radicals on the polysaccharide backbone 15 itself, leaving little scope for homopolymer formation, 16 if at all. Studies on homopolymerization by Owen and Shen 17 indicate that a monomer concentration of less than 2.0M and a ceric ammonium nitrate concentration of less than 0.1M did not result in homopolymerization.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, side reactions of the strong oxidation agent Ce IV [E ≈ +1.7 V vs. normal hydrogen electrode (NHE)] with the organic material in the acidic solutions (pH 2-3) are known to occur. [42] Nevertheless, the results from a series of experiments clearly showed that upon adding Ce IV to suspensions of Chara corallina cell walls, a small, but significant amount of O 2 was formed in the initial phase of the experiments (the first 2-3 min.). The maximum concentrations of O 2 were much higher than those found in control experiments, in which, for example, only acid was injected into the measurement cell.…”
Section: Water-oxidation Catalysismentioning
confidence: 94%